Impaired Cerebral Autoregulation Using Near-Infrared Spectroscopy and Its Relation to Clinical Outcomes in Premature Infants (2011)
The concordance between the change in the Mean Arterial Blood Pressure (MABP) and the Cerebral Blood Flow (CBF) is studied using the Correlation, Coherence and Partial Coherence methods in order to detect Impaired Cerebral Autoregulation in Neonates. The presence of impaired autoregulation is assessed by the use of the Critical Percentage of Recording Time (CPRT). The changesinCBF are reflected by the measurement of changesin cerebral intravascular oxygenation (HbD), regional cerebral oxygen saturation (rSO2), and cerebral tissue oxygenation (TOI), as measured by Near-Infrared Spectroscopy (NIRS) (INVOS4100 and NIRO300). The relation between impaired autoregulation and long term clinical outcomes in premature infants is studied.